Mechanisms of anti-hypertensive effect of standardized aqueous-ethanolic extract of ficus deltoidea kunstleri in spontaneously hypertensive rats / Norasikin Ab Azis - Ab Azis, Norasikin (2019)
In Malaysia, the prevalence of hypertension has increased over the last 10 years. Considering the current trends in the prevalence of hypertension in Malaysia, it can be speculated that there will be further increases in the number of individuals with cardiovascular diseases, leading to increased healthcare related economic burden. Among the factors that contribute to the poor control of hypertension is poor compliance to treatment. On that note, herbs, which occupy an important place in society have been actively investigated for their pharmacological potential. In this regard, Ficus deltoidea plant has attracted attention of researches over the last few years. It has been scientifically proven to possess wide range of pharmacological activities, which include anti-diabetic, wound healing and anti-oxidant properties. The data on the effect of this plant on blood pressure are non-existent. Hence, this study investigated the blood pressure lowering effect of standardized aqueous-ethanolic extract of leaves of Ficus deltoidea Kunstleri (FDK extract) in spontaneously hypertensive rats (SHR). The possible mechanisms of its anti-hypertensive effect were also investigated. Firstly, the dose dependent effect of FDK extract was determined using 4 different doses (500, 800, 1000, 1300 mg. Kg-1) that were administered orally for 4 weeks to SHR. Blood pressure was measured weekly using tail-cuff plethysmography. Besides blood pressure, body weight, urine output, food and water intake were also measured weekly. Subsequently, using the most effective dose, the effect of FDK extract on renin-angiotensin-aldosterone system (RAAS), endothelial function and anti-oxidant status was examined. Urine was subjected to 1H-NMR metabolomics and kidney tissue for gene expression studies. Systemic effects of FDK extract were studied by measuring liver and kidney functions as well as morphological features of kidney, aorta and heart. In the dose-response study, 1000 mg.kg-1 dose had the largest blood pressure lowering effect, based on area under time versus response curve (AUC). When compared to the control group, FDK extract treated rats showed lower concentration of angiotensin I, angiotensin II, aldosterone and angiotensin converting enzyme (ACE) activity. In addition, FDK extract treated rats showed higher concentration of ACE2 and angiotensin 1-7 in the serum. RT-PCR showed significantly greater ACE2 gene expression in the kidney of FDK extract treated group compared to vehicle treated group. FDK extract treated rats had improved endothelial function as evidenced from the higher concentration of eNOS in this group compared to vehicle treated group. FDK extract treated rats also exhibited higher serum total anti-oxidant capacity (TAC) compared to that in the vehicle treated group. Additionally, urinary metabolomic studies revealed altered levels of amino acids, ketone bodies and substances involved in energy metabolism and oxidative stress in the FDK extract treated group, indicating its antioxidant properties in its anti-hypertensive effect. The gene expression for FOXO3a, SOD2 and catalase were significantly greater in the kidney of FDK extract treated group compared to vehicle treated group. No changes were observed in liver and kidney functions as well as in the morphology of kidney, heart and aorta of FDK extract treated group, indicating absence of significant adverse effects of FDK extract at the dose used. In conclusion, administration of 1000 mg.kg-1 of standardized aqueous-ethanolic extract of leaves of FDK reduces blood pressure in SHR by reducing RAAS activity and improving endothelial function and redox status. These effects of FDK extract seem to be associated with changes in several metabolic pathways, which include amino acid metabolism, synthesis and degradation of ketone bodies and energy metabolism